Efficacy of Denosumab for Osteoporosis in Two Patients with Adult-Onset Still’s Disease—Denosumab Efficacy in Osteoporotic Still’s Disease Patients - Kumaki, Daiki (J Clin Med, 2018)
Adult-onset Still’s disease (AOSD) is an autoimmune inflammatory disorder. Glucocorticoids are often used for AOSD, which may induce complicating glucocorticoid-induced osteoporosis (GIO). An anti-resorption drug, denosumab, has recently been approved for osteoporosis treatment in Japan. However, the drug’s efficacy for GIO in AOSD is largely unknown. This retrospective, consecutive case series investigated two patients with GIO in AOSD to examine the effects of denosumab on bone metabolism. Bone turnover markers, and bone mineral density (BMD) of the lumbar 1–4 spine (L-BMD) and bilateral total hips (H-BMD) were followed for six months in a male patient and for twelve months in a female patient. No fractures or severe side effects, such as hypocalcemia, were observed during the observational period. Bone turnover markers were basically suppressed, and L-BMD and H-BMD were increased by denosumab in both patients. Our findings suggest that denosumab is a suitable candidate drug for GIO in AOSD.